PENGEMBANGAN WIRAUSAHA MELALUI DIGITALISASI OLEH KAGAWA HUMAN RING COOPERATIVE DAN KADIN SEMARANG: PENGEMBANGAN WIRAUSAHA MELALUI DIGITALISASI OLEH KAGAWA HUMAN RING COOPERATIVE DAN KADIN SEMARANG - Lispridona Diner; Tommi Yuniawan; Rina Supriatnaningsih; Lisda Nurjaleka; Silvia Nurhayati; Kazuhiko Miyauchi; Arnaz Agung Andrarasmara (Jurnal Pengabdian Masyarakat Multidisiplin, 2025)
The business world in Indonesia is developing rapidly, especially in the export-import sector and the industrial economy. Entrepreneurs play a vital role in the national economy, and the Chamber of Commerce and Industry (Kadin) functions as a companion organization to support the development of these businesses. The need to understand promotional techniques and business innovation is the main obstacle for entrepreneurs in Semarang. To overcome this challenge, the use of digital technology is a relevant solution. Therefore, the Japanese Language Education Study Program at Semarang State University collaborates with Human Kagawa Ring Cooperative Japan to provide an understanding of digital innovation in the business world. This community service activity carried out digital innovation training aimed at increasing the understanding of entrepreneurs in Semarang regarding technology that supports industrial activities. This one-day training also involves collecting data through questionnaires and interviews, which will be evaluated to support entrepreneurial development through digitalization. Based on the pre-test and post-test results, 40% of the participants were initially in the "less than" category, indicating an initial limitation in understanding digitalization. After the training, however, no participants were in the "below average" category, proving that the training method successfully raised the level of understanding of all participants.